The effect of beta vulgaris l juice on the acceleration of reducing the incidence of anemia in pregnant women - Sinaga, Ribur; Dewi, Eva Ratna; Pinem, Srilina; Purnamasari, Eka; Sagala, Rohhasianti; Yun, Deby Cyntia; Ertilida, Yusnita; Pasaribu, Novalita Eudia; Gulo, Marpiani (Institute of Computer Science (IOCS), 2024)
The largest issue affecting mother and child health in industrialized nations with a population of 1.62 billion is anemia (1). Since using medications and supplements for the treatment of anemia sometimes results in adverse consequences, eating beets is an option (2). the number of anemia cases, as well as to maintain healthy pregnancy and minimize the usage of contemporary treatment. From planning to the outcomes, the phases of the research process are executed in compliance with the established research flow diagram. There are thirty pregnant women at the Deby Midwifery Clinic that make up the study's sample. A pre-post experimental design was used for the study, with 15 participants receiving juice and another 15 serving as the control group. Ha is accepted and Ho is rejected, indicating an acceleration, according to the statistical analysis of the paired t test data in the above table, which shows a significance value (ρ) of 0.000 < (0.05). lessen anemia following beetroot juice use.